Apply PTTL Phenomenon Using Detectors Ultra Sensitivity Type MCP-N - Hiba Musadaq Salim (African Journal of Advanced Pure and Applied Sciences, 2023)
The use of solid-state detectors has been the primary focus of radiation dosimetry. Reevaluating the dosage using the phenomenon Photo-transferred thermoluminescence PTTL may lead to more thorough findings directly relevant to protecting those exposed to ionizing radiation. Researchers examined the usefulness of TL detectors at (0.5, 1, 2, 5, 10, and 25) mGy. Data from experiments show that when UV light of wavelength λ = 302 nm is applied and 80 °C for 2 h. TL signal appears, but this signal is sufficient to calculate the dosage of the previously read detectors for doses less than 25 mGy. PTTL are not appropriate for a dose reassessment in MCP-N detectors at the high dose. In addition, the count difference expected from a dosage variation of a few mGy is more than the standard deviation of the count figures. The number of PTTL cells often decreases as dosage rises. The number of PTTL for a 25 mGy dosage is much lower than that for a lowe doses. It is reasonable to suppose that, for doses low than 25 mGy, the correlation between dosage and PTTL counts becomes relevant for reevaluating the dose.